KOE e-learning assessment SOP V01 - Mohamed Azmin, Nor Fadhillah; Mohd Ali, Afifah; Rosli, Adib Hamdani; Mohd Zaki, Syazwani (2021)
This guideline is prepared for the Kulliyyah of Engineering lecturers on behalf of the kulliyyah’s e-learning teaching and learning committee.